The curse of Cain : the violent legacy of monotheism - Schwartz, Regina M. (Chicago : University of Chicago Press, 1997)
"A murderer, an outcast, a man cursed by God and exiled from his people - Cain, the biblical killer of Abel, is a figure of utter disdain. But that disdain is curiously in evidence well before his brother's death, as God inexplicably refuses Cain's sacrifice while accepting Abel's. Cain kills in a rage of exclusion, yet it is God himself who has set the brothers apart." "For Regina Schwartz, we ignore the dark side of the Bible to our peril. The perplexing story of Cain and Abel is emblematic of the tenacious influence of the Bible on secular notions of identity - notions that are all too often violently exclusionary, negatively defining "us" against "them" in ethnic, religious, racial, gender, and nationalistic terms. In this compelling work of cultural and biblical criticism, Schwartz contends that it is the very concept of monotheism and its jealous demand for exclusive allegiance - to one God, one Land, one Nation or one People - that informs the model of collective identity forged in violence, against the other." "The Hebrew Bible is filled with narratives of division and exclusion, scarcity and competition, that erupt in violence. Once these narratives were appropriated and disseminated by western religious traditions, they came to pervade deep cultural assumptions about how collectives are imagined - with collective hatred, with collective degradation, and with collective abuse. Recovering the Bible's often misguided role as a handbook for politics and social thought, Schwartz demonstrates just how dangerous it can be."--BOOK JACKET.
Includes bibliographical references (p. 177-202) and index.
Keywords: Ethnicity -- Biblical teaching; Ethnology in the Bible; Violence -- Religious aspects; Monotheism